Does income inequality hamper human capital accumulation in OECD countries? - Jakub Bartak (Managerial Economics, 2018)
The purpose of this article is to verify whether income  nequality impedes the accumulation of human capital in OECD countries during the years of 1990–2010. The article reviews theoretical findings that suggest a negative impact of income dispersions on human capital, and subsequently, it presents estimations of a dynamic model of human capital accumulation. The results of the study reveal a negative and statistically significant relationship between income inequality and human capital inflow measured as student skills test scores.